Investigating the Effect of Growth Phase on the Surface-Layer Associated Proteome of Lactobacillus acidophilus Using Quantitative Proteomics - Klotz, Courtney; O'Flaherty, Sarah; Goh, Yong Jun; Barrangou, Rodolphe (Frontiers in Microbiology, 2017)
Bacterial surface-layers (S-layers) are semi-porous crystalline arrays that self-assemble to form the outermost layer of some cell envelopes. S-layers have been shown to act as scaffolding structures for the display of auxiliary proteins externally. These S-layer associated proteins have recently gained attention in probiotics due to their direct physical contact with the intestinal mucosa and potential role in cell proliferation, adhesion, and immunomodulation. A number of studies have attempted to catalogue the S-layer associated proteome of Lactobacillus acidophilus NCFM under a single condition. However, due to the versatility of the cell surface, we chose a multiplexing-based approach with the intention of accurately contrasting multiple conditions. In this study, a previously described lithium chloride isolation protocol was used to release proteins bound to the L. acidophilus S-layer during logarithmic and early stationary growth phases. Protein quantification values were obtained via TMT (tandem mass tag) labeling combined with a triple-stage mass spectrometry (MS3) method. Results showed significant growth stage-dependent alterations to the surface-associated proteome while simultaneously highlighting the sensitivity and reproducibility of the technology. Thus, this study establishes a framework for quantifying condition-dependent changes to cell surface proteins that can easily be applied to other S-layer forming bacterium